The Influence of Understanding Accounting and Utilization of Accounting Information Systems on the Quality of Financial Reports in Cooperative Businesses in the DKI Jakarta Region - Suci Hayatul Utami; Fitrawansyah Fitrawansyah; Didik Riyanto; Udin Saepudin (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine how the influence of accounting understanding and the use of accounting information systems on the quality of financial reports (Survey on Cooperative Enterprises in the DKI Jakarta Region). The research that will be conducted regarding the effect of understanding accounting and utilizing accounting information systems on the quality of financial reports refers to several relevant previous studies. This is necessary to know the position and the currentness of the research being conducted and can be used as a comparison or reinforcement for previous research. The population used in this study were cooperatives in the DKI Jakarta area, totaling 3,447 cooperatives. The sampling technique in this study used a purposive sampling method and obtained 97 samples. The results of the study show that understanding of accounting has a positive effect on the quality of financial reports in cooperative businesses in DKI Jakarta. Utilization of accounting information systems has a positive and significant effect on the quality of financial reports in cooperative businesses in the DKI Jakarta Region. Simultaneously understanding of accounting and utilization of accounting information systems has a significant positive effect on the quality of financial reports in cooperative businesses in the DKI Jakarta Region.